2015
DOI: 10.1039/c4ra16983b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing performance of Ni/La2O3 catalyst by Sr-modification for steam reforming of toluene as model compound of biomass tar

Abstract: Steam reforming of biomass tar with toluene as the model compound was studied using Sr-doped Ni/La 2 O 3 catalysts prepared using two methods, i.e. co-impregnation of Sr and Ni on La 2 O 3 support (Ni-Sr/La 2 O 3 catalyst) and sequential impregnation of Sr on Ni/La 2 O 3 catalyst (SNL catalyst), which were then calcined at various temperatures (500, 700, and 900 C). These two types of catalysts are found to possess better catalytic performance than the undoped Ni/La 2 O 3 catalyst at the same calcination tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 67 publications
(80 reference statements)
0
19
0
Order By: Relevance
“…[12][13][14] Therefore, it is very important to remove tar for the effective use of biomass gasification products. [20,21] However, the main drawback of Ni-based catalysts is their rapid deactivation due to coking and sintering of Ni metal at high temperature. [15][16][17][18][19] Ni is one of the suitable catalysts for the steam reforming of biomass tar due to its low cost and high tar-destruction activity.…”
Section: Doi: 101002/adma201604257mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Therefore, it is very important to remove tar for the effective use of biomass gasification products. [20,21] However, the main drawback of Ni-based catalysts is their rapid deactivation due to coking and sintering of Ni metal at high temperature. [15][16][17][18][19] Ni is one of the suitable catalysts for the steam reforming of biomass tar due to its low cost and high tar-destruction activity.…”
Section: Doi: 101002/adma201604257mentioning
confidence: 99%
“…[15][16][17][18][19] Ni is one of the suitable catalysts for the steam reforming of biomass tar due to its low cost and high tar-destruction activity. [20,21] However, the main drawback of Ni-based catalysts is their rapid deactivation due to coking and sintering of Ni metal at high temperature. [22,23] Porous supports can improve the performance of Ni catalysts due to their increased surface area and improved particle dispersion.…”
Section: Doi: 101002/adma201604257mentioning
confidence: 99%
“…They found that the Ni catalyst supported on the pre-calcined Ce-Zr prepared by wet impregnation had smaller crystallite size of Ni, higher surface area and higher Ni dispersion, compared with the in-house calcined Ce-Zr supported Ni catalysts prepared by wet and dry impregnation, as shown in Table 4. Oemar et al [118] prepared two kinds of Sr-doped Ni/La 2 O 3 catalysts for steam reforming of toluene as a model tar compound. Co-impregnation and sequential impregnation methods were used to prepare A Ni-Sr/La 2 O 3 catalysts.…”
Section: Influences Of Preparation and Pre-treated Methodsmentioning
confidence: 99%
“…Over the years, the catalysts used in the steam reforming of TARs have been based primarily on transition metals. Nickel supported on oxides can be highlighted among these transition metals [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Specifically, a variety of works have focused on the study of Ni catalysts supported in alumina such as Ni/gamma-Al2O3-SiO2 with different silicon precursors [44], nickel catalysts supported on hexaaluminates [45], Ni-doped γ-Al2O3 [46], Ni/Ce-Al2O3 [47], etc.…”
Section: Introductionmentioning
confidence: 99%